Binary Quantum Communication using Squeezed Light: Theoretical and Experimental Frame Work (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The aim of this paper is to develop framework to generate squeezed light for binary quantum communication. Both theoretical and experimental models to generate squeezed state  using optical parametric amplifier (OPO), which is implemented around He-Ne laser, are described in details.  The results will be used as a guide line to investigate the performance of squeezed light-based quantum communication over noisy channel and this issue will be presented in accompanying paper [1].